Introduction to the special issue on Locating and theorising platform power - David Nieborg; Thomas Poell; Robyn Caplan; José van Dijck (Internet Policy Review, 2024)
Against the backdrop of ongoing public and political debates about the power and regulation of large platform conglomerates, this special issue calls for more critical, conceptual, and empirical studies on platform power. While a lot of valuable research has already been done, we see a tendency in both public and scholarly debates on leading platform companies to develop one-sided, monolithic understandings of this power. Instead, we want to argue for a relational perspective, which focuses on the relations of dependence that grow around specific platforms. Therefore, contributions locate and theorise platform power. Through specific case studies on particular types of platforms the contributions home in on the various modalities of power. The papers address three broader themes that speak to the different facets of platform power: (1) analysing platform infrastructures and markets; (2) platform governance; (3) the negotiation of platform power and its alternatives.
Keywords: 300; Platform power; Governance; Infrastructure; Markets; Relational